Threshold Conditions for the Shift Between Vegetated and Barebed Rivers. Issue 1 (9th January 2022) - Calvani, G.; Carbonari, C.; Solari, L.
Abstract: Vegetation plays a fundamental role in riverine environments, by affecting both hydrodynamics and morphodynamics. At the same time, flow velocity and sediment scouring influence the decay of plants by uprooting. The balance among such interactions defines whether or not rivers are colonized by submerged or emergent vegetation. Previous studies focused on the shift between vegetated and barebed conditions through flume experiments or numerical simulations. Herein, we derive analytical formulations for the threshold in terms of flow velocity and Froude number, by accounting for the conditions of submergence. Both the formulations predict lower thresholds for submerged vegetation than emergent plants. Vegetation characteristics and flow regime variability play the major role in controlling the thresholds. The comparison of the proposed relationships to available data shows a good agreement. These results have important implications to understand bio‐morphological changes induced by natural and human factors, as well as to design effective river restoration projects. Plain Language Summary: Fluvial systems are amongst the most biologically and economically important environments. The interactions between water, sediments, ecological components, as well as human interventions lead to the developments of different riverine habitats. In this work we refer to the presence or not of submerged plants, generally growing in water and emergent vegetation, generally riparian shrubs and trees growing on riverbanks. We provide simple formulations to discriminate conditions for which plant species may colonize and survive in a given fluvial environment. The critical conditions are derived in terms of the mean flow velocity and the Froude Number, a dimensionless quantity relating flow velocity to the water depth. We tested the proposed formulations against data from real rivers and highlighted that submerged vegetation shows lower values of the threshold quantities than emergent plants. Besides other factors, the analysis may explain why submerged plants are less common in large rivers and paves the way to understand the evolution of the riverine systems subject to climate change, colonization by invasive species and human interventions. Key Points: Formulations for the threshold conditions between vegetated and barebed channel are derived Threshold conditions are mainly related to species‐dependent characteristics Submerged plants are more vulnerable to removal than emergent as relative emergence reduces the threshold value